(untitled) (Fiep Bulletin - online, 2014)
Overweight and childish obesity show an elevated prevalence and multi-factorial character. The alterations on arterial pressure, on the glycemic rate, on the IMC and on the waist and hip perimeter suggest that obesity contributes for the metabolic syndrome. The objective of this research was to identify the anthropometric profile, fast glycemia, arterial pressure and risk of metabolic syndrome in children from 3 to 7 years old. 116 pre-scholars were valuated, from both genders, the used tests were: weight, height, waist-hip, glycemia and arterial pressure. The children were classified as euthrophic, over weighted and obese in agreement to the IMC. The measure of the first waist-hip perimeter had a significant comparison. In the glycemia test, 12 boys (17, 64 %) and 10 girls (20, 83 %) presented fast glycemia over 120 mg/dL. The medium average was of 95 mg/dL, considered normal for the age. The arterial pressure showed, inside the parameters of normality. The prevalence of overweight and obesity together, reached 10, 3 % of the boys and 5, 17 % of the girls. The averages of the measures of the waists and hips of boys and girls (52, 2 cm and51, 2) were significant different from those who are obese (63, 0 and 58, 2 cm). There wasn’t any difference on the waists-hips measures between the groups. The prevalence of one and two components of the metabolic syndrome was of 18, 96 and 8, 62 %, respectively. Two children presented 3 components of metabolic syndrome, being the disease found. Concluding, the level of adiposity was bigger for the masculine sex, on the fast glycemia test 12 boys (17, 64 %) and 10 girls (20, 83 %) presented fast glycemia above 120 mg/dL, 2 children presented PA of 135/85. Generally, children showed a high risk for metabolic syndrome.